DOI: 10.11606/d.76.2019.tde-30092019-141547
|View full text |Cite
|
Sign up to set email alerts
|

Análise teórica da topologia da densidade de carga eletrônica em sistemas periódicos tridimensionais

Abstract: Trabalho dedicado à memória de minha mãe Maria Izabel e de meu pai Arnóbio que, apesar do pouco grau de instrução, souberam transmitir a noção de se fazer boas escolhas e de que estudar, sempre será a melhor opção. Dedicado à minha companheira Regina pelo apoio em minhas escolhas e decisões. Também é dedicado à Ciência, essa maravilhosa e encantadora musa que tem sido covardemente atacada, justamente quando se esperava paixão e valorização por suas contribuições ao avanço tecnológico e à melhora da expectativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The experimental model was compared with those derived from corresponding theoretical calculations for solid-state and gas-phase conditions using density functional theory (DFT) methods at the B3LYP\6-311++G** level of theory. [5] The detailed study of the molecular electron density, its corresponding topology and charge distribution were based on the quantum theory of atom in molecules (QTAIM). [6] The charge density distribution and analysis of topological properties revealed that the C-F bond may have a transit closed-shell configuration (Fig.…”
mentioning
confidence: 99%
“…The experimental model was compared with those derived from corresponding theoretical calculations for solid-state and gas-phase conditions using density functional theory (DFT) methods at the B3LYP\6-311++G** level of theory. [5] The detailed study of the molecular electron density, its corresponding topology and charge distribution were based on the quantum theory of atom in molecules (QTAIM). [6] The charge density distribution and analysis of topological properties revealed that the C-F bond may have a transit closed-shell configuration (Fig.…”
mentioning
confidence: 99%